Who counts as Filipino? Philosophical issues of identity and the Chinese Filipino - Dela Cruz, Noelle Leslie (2015)
This article examines some recent philosophical attempts to make sense of “identity” in light of the intersecting categories of race, ethnicity, and culture. It addresses a perennial issue brought up recently with regard to Filipino Chinese: Who counts as “Filipino?” Behind this question are assumptions that I scrutinize philosophically: that there is a “Filipino” and it is possible to identify who counts as such and who does not. I begin with a survey of existing paradigms of identity which I then apply to a critical analysis of recent public discourse spawned by anti-Chinese statements made by a prominent Filipino novelist. I conclude with ethical prescriptions for conceptualizing Filipino identity in light of the complex fissures revealed by the aforementioned issue.
Keywords: Nationalism; Identity (Philosophical concept)